Perspectives on Human Trafficking and Modern Forms of Slavery - Kara, Siddharth (Social Inclusion, 2015)
When I first began researching human trafficking and modern forms of slavery fifteen years ago, there was very limited awareness of these offences, and even less scholarship. While non-profit organizations, activists, and charitable foundations have worked assiduously to raise awareness of human trafficking and to tackle root causes, investment by the academic community to analyze the nature, scale, and functioning of the phenomena has been slower to evolve. Indeed, much of the confusion relating to basic terms and concepts on the topic of modern forms of slavery has been due, in large part, to the lack of scholarly analysis of the issues. Following on this gap has been a dearth of robust, first-hand field research that can guide scholarship, investment, and activism, and help frame the complex questions relating to law, economics, human rights, gender, poverty, corruption, migration, the rights of children and minorities, and many other issues that are fundamental to our understanding of human trafficking.